Thrifting dalam Perspektif Maqashid Syari’ah - Rafi Nur Azizah; Imam Kamaluddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the practice of selling imported used clothing (thrifting) from the perspective of maqashid shariah. Thrifting has become a popular trend due to the development of technology and the demand for affordable fashion. However, in Indonesia this practice is prohibited based on the Regulation of the Minister of Trade (PERMENDAG) No. 18 of 2021, Article 2 Paragraph 3 No. 18 of 2021, and Law of the Republic of Indonesia No. 7 of 2014 which prohibits the export and import of used clothing, used bags, and used sacks. This practice also contains polemics regarding its legality and impact on the local economy and public health. Thrifting is also included in the waste of developed countries with reuse that tarnishes Indonesia's image in the eyes of the world. This study uses a descriptive qualitative approach with analysis of secondary sources such as journals, books, articles, and sources relevant to thrifting. The results of this study indicate that the practice of thrifting is not in accordance with maqashid ‎sharia because 1) Hifdzu Diin encourages tabdzir behavior, 2) Hifdzu Nafs spreads disease 3) Hifdzu Aql fosters a consumerist mindset, 4) Hifdzu Nasl has the potential to spread disease across generations 5) Hifdzu Mal is detrimental to individual or group economic management. This study emphasizes the importance of harmonizing regulations that support the local economy and protect the interests of the community. Support from the government, community, and stakeholders is needed to realize this sustainability.